The characteristics of the medicinal plants used in the herbal medicine оf type 2 diabetes - Калмыков, Сергей; Калмыкова, Юлия (Slobozhanskyi Herald of Science and Sport, 2016)
Sergei Kalmykov, Julia Kalmykova Purpose: consider the rational combination of the herbs in fytocomplexes applied in the rehabilitation of the type 2 diabetes. Material & Methods: analysis of scientific and methodical literature on the use of herbal medicine in the complex rehabilitation for patients with diabetes. Results: modern views on the necessity and the features of the use of herbal remedies especially in the diabetes type 2 are presented; the main medicinal plants used in this pathology are described. The main attention is paid to the peculiarities of forming up an integrated cure that contains a mixture of several kinds of medicinal plants. The classification of herbal drugs used for diabetes is given. Conclusions: advantages of application of collection of medicinal plants over synthetic drugs in the complex treatment of the type 2 diabetes are proved.